Air pollution monitoring system based on air pollutant index(API) and geographic information system(GIS) - Auvee, Md. Samiul Bashar (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.